Opposition to capital market opening - Philipp Engler; Alexander Wulff (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
We employ a neoclassical growth model to assess the impact of financial liberalization in a developing country on capital owners` and workers` consumption and welfare. We find in a baseline calibration for an average non-OECD country that capitalists suffer a 42 percent reduction in permanent consumption because capital inflows reduce their return to capital while workers gain 8 percent of permanent consumption because capital inflows increase wages. These huge gross impacts contrast with the small positive net effect found in a neoclassical represent agent model by Gourinchas and Jeanne (2006). We further show that the result for capitalists is insensitive to enhanced productivity catch-up processes induced by capital inflows. Our findings can help explain why poorer countries tend to be less financially open as capitalists` losses are largest for countries with the lowest capital stocks, inducing strong opposition to capital market opening.
Keywords: F2; F3; F43; E13; E25; O11; 330; Capital flows; international financial integration; growth; neoclassical model; heterogenous agents